ANALISIS GHARAR DALAM JUAL BELI PAKAIAN BEKAS KARUNGAN - Nurniati, Nurfadila (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
The main problem in this research is, First, what is the buying and selling transaction for used sack clothes? Second, what is the gharar analysis of buying and selling transactions of used sack clothes? This type of research is qualitative research with a phenomenological approach. Secondary data comes from various sources, namely books, journals and other research. The data collection method used was observation, interviews and documentation. Data analysis was carried out through three stages, namely data reduction, data presentation and drawing conclusions. Consumers of used clothes are expected to be able to weigh and choose the goodness of using used clothes.